1997
DOI: 10.1074/jbc.272.45.28557
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NEDD8, a Developmentally Down-regulated Ubiquitin-like Protein

Abstract: NEDD8 is a novel 81 amino acid polypeptide which is 60% identical and 80% homologous to ubiquitin. Northern blot analysis showed that the NEDD8 message was developmentally down-regulated. In adult tissues, NEDD8 expression was mostly restricted to the heart and skeletal muscle. Antiserum specific for NEDD8 detected a 6-kDa monomer in SK-N-SH, BJAB, and HL60 cell lysates. A 14-kDa band was also detected in BJAB, HL60, and SK-MEL28 but not in SK-N-SH and K562 cell lysates. An approximately 90-kDa band was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
368
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(391 citation statements)
references
References 24 publications
14
368
0
Order By: Relevance
“…Early studies demonstrated that cullin neddylation is required for efficient ubiquitylation and/or turnover of CRL substrates in vivo, which has been borne out through the development of MLN4924, a small-molecule inhibitor of NAE [14,[48][49][50]. Inhibition of CRL activity by MLN4924 results in accumulation of a host of CRL targets [14,43,51,52].…”
Section: Mechanism Of Cullin Neddylationmentioning
confidence: 99%
“…Early studies demonstrated that cullin neddylation is required for efficient ubiquitylation and/or turnover of CRL substrates in vivo, which has been borne out through the development of MLN4924, a small-molecule inhibitor of NAE [14,[48][49][50]. Inhibition of CRL activity by MLN4924 results in accumulation of a host of CRL targets [14,43,51,52].…”
Section: Mechanism Of Cullin Neddylationmentioning
confidence: 99%
“…The RING domain of IAPs acts as an E3 ligase, leading to ubiquitination of IAPs themselves and their client proteins, such as caspases. Recent studies discovered that neuronal precursor cell‐expressed developmentally downregulated protein 8 (NEDD8), a ubiquitin‐like protein,17 is activated by IAPs in the regulation of apoptosis through neddylation of caspases 18, 19, 20. IAPs function in ways beyond inhibition of apoptotic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of NEDD8 expression was observed in various human tumor cell lines, such as leukemia, HeLa, K562, and MOLT-4 cells but was low in Raji, SW480, and G361 cells. No appreciable change in the NEDD8 expression was observed during embryonic development of mice, although it was reported to be down-regulated developmentally (Kumar et al, 1993;Kamitani et al, 1997).…”
mentioning
confidence: 96%